Effects of the Vibration Amplitude in Vibratory Stress Relief on the Fatigue Life of Structures - Bui Manh, Cuong; Nguyen Van, Duong; Do Van, Si; Phan Van, Manh; Le, Van Thao (Advances in Technology Innovation, 2021)
This research aims to investigate the effects of vibration amplitude in vibratory stress relief (VSR) on the fatigue strength of structures with residual stress. Experiments are carried out on specimens with residual stress generated by local heating. Flat specimens made of A36 steel are prepared to be suitable for setting up fatigue bending tests on a vibrating table. Several groups of samples are subjected to VSR at resonant frequencies with different acceleration amplitudes. The results show that VSR has an important influence on the residual stress and fatigue limit of steel specimens. The maximum residual stress in the samples is reduced about 73% when the amplitude of vibration acceleration is 57 m/s2. The VSR method can also improve the fatigue limit by up to 14% for steel samples with residual stress.